Oscillation of Superlinear second Order Nonlinear Differential Equations with Damping Term - Salhin, Ambarka A. (Scientific Journal for Faculty of Science-Sirte University, 2023)
The study of differential equations has been the object of many researchers over the last decades. Different approaches and various techniques have been adopted to investigate the qualitative properties of their solutions. Recently and driven by their widespread applications, the investigation of differential equations of second order has drawn significant attention. The oscillation of solutions has been the main features that have attracted consideration. Therefore, it has been intended to use the Riccati Transformation Technique for obtaining several new oscillation criteria for different classes of nonlinear differential equations of the second order with a damping term. Oscillatory behavior has taken into account through this study of solutions of some differential equations. Comparisons between our results and the previously known results have presented. The relevance of our theorems has been clear clear due to carefully selected examples. As a conclusion, our aim is to provide some results to improve and/or extend some of well-known results in the literature.